Non-Puerperal Uterine Inversion. Issue 1 (10th March 2016) - Leconte, Isabelle; Thierry, Cecile; Bongiorno, Antony; Luyckx, Mathieu; Fellah, Latifa
We report a case of non-puerperal uterine inversion, illustrating the correlation between MRI and pre-operation macroscopic images.